My lady Jane - Hand, Cynthia, 1978- (HarperTeen, an imprint of HarperCollinsPublishers, 2016)
"Lady Jane Grey, sixteen, is about to be married to a total stranger--and caught up in an insidious plot to rob her cousin, King Edward, of his throne. But that's the least of Jane's problems. She's about to become Queen of England. Like that could go wrong"--Dust jacket.